2022
DOI: 10.1186/s13054-022-04064-3
|View full text |Cite
|
Sign up to set email alerts
|

Lung ultrasound response to awake prone positioning predicts the need for intubation in patients with COVID-19 induced acute hypoxemic respiratory failure: an observational study

Abstract: Background Awake prone positioning (APP) reduces the intubation rate in COVID-19 patients treated by high-flow nasal cannula (HFNC). However, the lung aeration response to APP has not been addressed. We aimed to explore the lung aeration response to APP by lung ultrasound (LUS). Methods This two-center, prospective, observational study enrolled patients with COVID-19-induced acute hypoxemic respiratory failure treated by HFNC and APP. LUS score wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 28 publications
0
20
0
Order By: Relevance
“…Other studies have investigated the aeration response to aPP in patients with acute respiratory failure related to COVID-19 using ultrasound scores [ 26 29 ]. Consistent results were observed with an improvement in aeration of the dorsal regions of the lungs during and after aPP, particularly in patients who benefited from the combination of aPP and high-flow O 2 nasal cannula [ 26 , 28 ] or non-invasive ventilation [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…Other studies have investigated the aeration response to aPP in patients with acute respiratory failure related to COVID-19 using ultrasound scores [ 26 29 ]. Consistent results were observed with an improvement in aeration of the dorsal regions of the lungs during and after aPP, particularly in patients who benefited from the combination of aPP and high-flow O 2 nasal cannula [ 26 , 28 ] or non-invasive ventilation [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…They found that lung ultrasound assessment was more sensitive than the changes in oxygenation and respiratory rates. The reduction of LUS in the dorsal areas ≥1 point after the first APP session was associated with a decreased risk for intubation in patients undergoing APP (relative risk 0.25 [0.09–0.69]) [34 ▪ ]. Additionally, both Ibarra-Estrada et al .…”
Section: How To Assess Patient Response To Awake Prone Positioning?mentioning
confidence: 89%
“…Additionally, both Ibarra-Estrada et al . [34 ▪ ] and Musso et al . [36 ▪ ] found that longer APP duration was correlated with a higher reduction in LUS.…”
Section: How To Assess Patient Response To Awake Prone Positioning?mentioning
confidence: 91%
See 1 more Smart Citation
“…Moreover, awake patients with spontaneous breathing during prone positioning could lead to improved gas exchange, decreased inspiratory effort and lung stress, and attenuated systemic in ammatory response (23). A recent study also demonstrated that for patients with COVID-19induced acute hypoxemic respiratory failure (AHRF) and treated by high ow nasal cannula oxygen therapy (HFNC) and APP, APP was associated with improvements of the aeration of the dorsal lung zones (24). These might explain the effects of awake prone position in avoiding intubation.…”
Section: Discussionmentioning
confidence: 99%